Heteroaryliodonium(III) Salts as Highly Reactive Electrophiles - Takenaga, Naoko; Kumar, Ravi; Dohi, Toshifumi (Frontiers in Chemistry, 2020)
In recent years, the chemistry of heteroaryliodonium(III) salts has undergone significant developments. Heteroaryliodonium(III) salts have been found to be useful synthetic tools for the transfer of heteroaryl groups under metal-catalyzed and metal-free conditions for the preparation of functionalized heteroarene-containing compounds. Synthetic transformations mediated by these heteroaryliodonium(III) salts are classified into two categories: (i) reactions utilizing the high reactivity of the hypervalent iodine(III) species, and (ii) reactions based on unique and new reactivities not observed in other types of conventional diaryliodonium salts. The latter feature is of particular interest, and so has been intensively investigated in recent decades. This mini-review therefore aims to summarize the recent synthetic applications of heteroaryliodonium(III) salts as highly reactive electrophiles.